(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study aims to improve the sustainability and performance of asphalt mixtures by extracting binder from Reclaimed Asphalt Pavement (RAP) and incorporating waste engine oil. Centrifuge, reflux, and vacuum extraction methods are used, with centrifuge preferred for preserving binder properties. Characterization of asphalt concrete components, including bitumen and aggregates, is crucial for optimizing mixture performance. A mixture was formulated with 25% RAP and 75% fresh aggregates, incorporating varying percentages of waste engine oil to enhance flowability and resistance to cracking. The Marshall Stability test showed that stability decreased with increased waste engine oil, while flow, air voids, and VMA increased. The extracted binder content from RAP was 4.53% by weight. This research supports sustainable infrastructure development by reusing RAP and waste engine oil, reducing environmental impact such as energy conservation, reduced pollution, resource recovery, wastes reduction, carbon footprint reduction and promoting durable pavements. It contributes to more efficient asphalt pavement construction practices, aligning with sustainable infrastructure goals by enhancing the reuse of recycled materials and minimizing waste. The study provides valuable insights into innovative methods for sustainable asphalt construction, promoting environmentally friendly practices in the infrastructure sector.